파랑관통형 고속활주선 선형개발에 관한 연구 - 정우철(Uh-Cheul Jeong); 이동건(Dong-Kun Lee); 정기석(Ki-Seok Jung) (Han-guk haeyang gonghak hoeji (Online), 2016)
A new wave-piercing-type high-speed planing boat without a chine was developed, and its basic performance was investigated in a model test, including the resistance, trim, and sinkage. The maximum speed of the developed ship was 35 knots. The hull form was developed by combining a VSV (very slender vessel) and TH (transonic hull), which have large deadrise angles at the bow. The main dimensions were estimated by a statistical approach using actual ship data. The effect of a side fin attached at the stern near the water line was investigated from a resistance point of view. It was found that the developed hull form showed the possibility of a new concept for a high-speed planing hull without a chine, and the side fin played an important role in increasing the resistance performance by controlling the trim and sinkage in the high-speed range.